Factors Affecting School-Based Mental Health in Adolescents: Scoping Review - Bergita Dumar; Heni Dwi Windarwati; Laily Yuliatun (Universitas Aisyah Pringsewu, 2023)
Background: Adolescence is a transition period from childhood to adulthood that experiences growth and development marked by physical, psychological, and social changes. Teenagers spend a lot of time in the school environment, so school is one of the places that can have a big impact on adolescent mental health. Objective: This Scoping Review aims to discuss the factors that can affect school-based mental health in adolescents. Methods: This scoping review uses articles from the last ten years (2013 - 2022). Determination of keywords using the PICO format in accordance with the topic scoping review. Search articles using databases such as EBSCO, Science Direct and Google Scholar according to the inclusion and exclusion criteria that have been determined. The article identification process uses the PRISMA Flowchart chart. Results: there were 19 articles reviewed with the same theme showing that several factors affect the mental health of adolescents in the school environment such as knowledge and information, peer relations, academic pressure and technology. Conclusion: It can be concluded that a school environment is a place that has a considerable influence on the emergence of several factors that can impact mental health in adolescents. Abstrak: Latar Belakang: Remaja merupakan masa transisi dari masa kanak-kanak ke masa dewasa yang mengalami tumbuh kembang ditandai dengan perubahan fisik, psikologis, dan sosial. Remaja menghabiskan banyak waktu di lingkungan sekolah, sehingga sekolah menjadi salah satu tempat yang dapat memberi dampak besar terhadap kesehatan jiwa remaja. Tujuan: Scoping Review ini bertujuan untuk membahas terkait faktor-faktor yang dapat mempengaruhi kesehatan jiwa berbasis sekolah pada remaja Metode: Scoping review ini menggunakan artikel 10 tahun terakhir (2013 - 2022). Penentuan kata kunci menggunakan format PICO sesuai dengan topik scoping review. Pencarian artikel menggunakan database seperti EBSCO, Science Direct dan Google Scholar sesuai dengan kriteria inklusi dan eksklusi yang sudah ditentukan. Proses identifikasi artikel menggunakan bagan PRISMA Flowchart. Hasil: terdapat 19 artikel ditinjau dengan tema yang sama menunjukkan bahwa terdapat beberapa faktor yang mempengaruhi kesehatan jiwa remaja dilingkungan sekolah seperti pengetahuan dan informasi, hubungan teman sebaya, tekanan akademik dan teknologi. Kesimpulan: Dapat disimpulkan bahwa lingkungan sekolah merupakan tempat yang memiliki pengaruh cukup besar terhadap munculnya beberapa faktor yang dapat memberi dampak terhadap kesehatan jiwa pada remaja.